Bohater heterogeniczny – opera, cyrk i kicz w filmie Filipa Bajona „Aria dla atlety” - Tomczyk-Jarzyna, Izabela (Załącznik Kulturoznawczy, 2023)
The author analyzing Filip Bajon’s film Aria for an Athlete focuses on the relationship between opera and circus, paying attention primarily to their interrelationship and not the differences. According to the author, the category common to both shows is kitsch. Any kind of art has in its history phase of kitsch, yet what is derived from the kitsch can become the beginning of art. While describing the coexistence of opera and circus, author makes a study of three movie characters: Władysław Góralewicz, clown Max and tenor Babtisto Messalini. In her opinion, these representatives of respectively the world of circus or the opera, have a number of attributes that allow to assign them the culture which is alien to them. Max, circus clown, elevates kitsch, but also shows a duality of nature of both commedia dell’arte and film, Góralewicz, artist-wrestler rooted in the circus, longs for the opera, singer Messalini, whose profession is to create a culture, brings to life kitsch.